Efektivitas Model Problem Based Learning untuk Meningkatkan Keterampilan Menulis Karangan Eksposisi pada Siswa Kelas X IPA 4 SMAN 4 Pandeglang Tahun Pelajaran 2021-2022 - Dahlia, Dahlia (Universitas Mathla'ul Anwar Banten, 2023)
This research aims to: 1) describe students' skills in the aspect of formulating titles in writing expository essays using the Problem Based Learning model; 2) describing the students' skills in the aspect of paragraph development including presenting information, unity, coherence, and assertiveness in writing expository essays using the Problem Based Learning model; and 3) describe students' skills in spelling and punctuation in writing expository essays using the Problem Based Learning model. This research is a classroom action research (PTK) with a location at SMAN 4 Pandeglang. Research instruments include observation sheets and expository essay writing skills tests. This research consists of 2 cycles. The results of the research show an increase in the results of writing expository essays. The improvement of the ability to write an exposition essay can be seen from the average ability and the ability of each aspect. The average ability of students in writing exposition essays increased from 65 to 75 in cycle 1 and increased by 15.38%, while the average in cycle 2 was 80 and increased by 6.66% from cycle 1.